Influences of E-commerce Adoption on Sales performance among Agrochemical Input Dealers in the Ghanaian City - Benjamin Nyarko; Nicholas Oppong Mensah; Kofi Agyenim Boateng; Anthony Donkor (Cogent Business & Management, 2022)
Purpose This study assessed the effect of E-commerce on sales performance of agrochemical input dealers in the Greater Accra Region of Ghana. Design/methodology/approach The study utilized both primary and secondary data. 10 Primary data was collected with semi-structured questionnaires to a sample of 125 respondents, consisting 105 adopters and 20 non adopters (E-commerce). Secondary data was collected from Ghana Agri-Input dealers association (GAIDA), Environmental protection Agency (EPA), libraries and through the internet. The propensity score matching (PSM) was used to analyse the effect of E-commerce on sales performance. Findings The adoption of E-commerce resulted in about GH₡ 11,456.07, GH₡ 10,317.62, GH₡ 11,176.68, GH₡ 11,025.37 increase in sales revenue for the monthly estimates whilst for the quarterly estimates the amount increased by GH₡ 40,690.29, GH₡ 36,089.43 GH₡ 39,538.42 and GH₡ 38,921.03. The result are suggestive that adopters of E-commerce are largely offered avenues distinct from the traditional marketing to attract customers and reduced necessary operational costs involved in sales. Thus, expanding firms' "reach" without compromising "richness" however, the decrease might be attributed to barriers to the effective and efficient implementation of E-commerce by agrochemical industries within the region. Originality/Value As E-commerce is an ongoing new trend that is predicted to be a crucial alternative to the use of market place centered on geographical location, and further aid in sales performance, there is the need for an insight into the effect of the adoption of E-commerce on sales to be established within the agrochemical industry.
Keywords: 650; E-commerce; agrochemical; average treatment effect; input dealers; propensity score matching